A Vote of Competence: How a Similar Upbringing to Political Candidates Influences Voting Choice. Issue 4 (October 2020) - Meng, Matthew D.; Davidson, Alexander
A common strategy employed by political leaders to win elections is to establish similarity with their constituents. This article extends previous research on this approach in several ways. First, the authors test and confirm the commonly used, but underresearched, political marketing tactic of highlighting similarity with constituents through upbringing characteristics. Second, given the debate about why the similarity-voting effect occurs, the authors aimed to establish causality of the effect. They found that perceived competence and liking both mediate this relationship in the context of similar upbringing. Finally, the positive effect of similar upbringing only holds for those with average and above-average self-perceptions of political skills, meaning that this approach would not be effective for some inexpert voting populations. By understanding the mechanism behind the similarity-voting effect in the context of similar upbringing, in addition to its important caveat, political marketers can approach campaigns in a more informed manner.